Religious identity and national heritage : empirical-theological perspectives - Anthony, Francis-Vincent.; Ziebertz, Hans-Georg, 1956- (Empirical Studies in Theology, 2012)
In some parts of our world, religion is on the wane, losing its thrust of doctrinal authority and communal bonds. In other regions, it is gaining public significance as a powerful social, cultural and political force. Secularization theories are less successful in accounting for these differences in religion's role. Other theories describe religion in terms of social capital to be invested whenever it offers certain personal, social or political benefits and market opportunities allow smart choices. Still other theories simply hold that religion corresponds to an inborn need or stable disposition that guarantees a culture's identity and reflects a natural equilibrium of social cohesion. There are also critical theories that point to the intrinsic relationship of religion with power and identify it as a major cause of tension and conflict. In this book distinguished scholars reflect on these questions and present empirical research about religious identity and national heritage.